2019
DOI: 10.1103/physrevd.100.124019
|View full text |Cite
|
Sign up to set email alerts
|

Overcharging higher curvature black holes

Abstract: We examine the problem of overcharging extremal and near-extremal black hole solutions of Einstein-Gauss-Bonnet gravity in any dimension, generalizing the result in general relativity. We show that as in the case of general relativity, it is not possible to create a naked singularity by overcharging an extremal black hole in Einstein-Gauss-Bonnet gravity using a charged test particle. Our result suggests that the validity of the cosmic censorship hypothesis transcends beyond general relativity to well motivate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Different with the result in [27], here we did not utilize the optimal condition of the first-order identity. As a result, we found that the static charged Gauss-Bonnet black holes cannot be overcharged by above collision process under the second-order approximation of perturbation, although they can be destroyed by the old version of the gedanken experiments as shown in [36]. Our result at some level implies that the WCCC can also be restored in the EMGB gravitational theory.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Different with the result in [27], here we did not utilize the optimal condition of the first-order identity. As a result, we found that the static charged Gauss-Bonnet black holes cannot be overcharged by above collision process under the second-order approximation of perturbation, although they can be destroyed by the old version of the gedanken experiments as shown in [36]. Our result at some level implies that the WCCC can also be restored in the EMGB gravitational theory.…”
Section: Discussionmentioning
confidence: 49%
“…As one of the most interest higher curvature gravitational theories, the Einstein-Maxwell-Gauss-Bonnet (EMGB) gravity is an important generalization of Einstein gravity, where the Gauss-Bonnet term can be regarded as a correction from the heterotic string theory [34,35]. In [36], the authors investigated the old version of the gedanken experiments in the charged static Gauss-Bonnet black holes and found that the near extremal case can also be overcharged. Therefore, in this paper, we would like to check whether the WCCC can be restored in the EMGB gravity if we consider the new version of the gedanken experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The solution for spherically symmetric charged BH with this gravity theory in D ‐dimension space‐time can be given as [ 58 ] ds2badbreak=G(r)dt2goodbreak+G1(r)dr2goodbreak+r2dΩd22\begin{equation} ds^{2}=-G(r)dt^{2}+G^{-1}(r)dr^{2}+r^2d{\Omega }^2_{d-2} \end{equation}where G(r)badbreak=1goodbreak+[]11+16βMrd18βq2r2d4r24β\begin{equation} G(r)=1+{\left[1-\sqrt {1+\frac{16\beta M}{r^{d-1}}-\frac{8\beta q^2}{r^{2d-4}}}\right]}\frac{r^2}{4\beta } \end{equation}where M , q , and β are BH mass, BH charge, and the BH coupling constant β̂$\hat{\beta }$ as β=(d3)(d4)trueβ̂/2$\beta =(d-3)(d-4)\hat{\beta }/2$, respectively. We study the space–time by dΩd22$d{\Omega }^2_{d-2}$ of the unit false(d2false)$(d-2)$ area of sphere Ad2$A_{d-2}$.…”
Section: Einstein–gauss–bonnet Gravity Theory Of Black Holesmentioning
confidence: 99%
“…The BH of spherically symmetric solution of this gravity theory in D-dimension spacetime is of the form [21]…”
Section: Einstein-gauss-bonnet Black Hole Gravity Theorymentioning
confidence: 99%